Bhatti Functional Scoring System Versus Other Clinical Scores for the Evaluation of Post-Surgical Reduction of Developmental Dysplastic Hips. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the accuracy and validity of Bhatti Functional Scoring System (BFSS) for the evaluation of post-surgical reduction of Developmental Dysplastic Hips versus clinical evaluation systems designed by Ferguson and Howarth and McKay’s clinical Criteria.Methods: This cross-sectional study included patients with Developmental Dysplastic Hips operated for open reduction during 1st June 2016 to 30th June 2017 with minimum follow up duration of one year. The study was conducted in Department of Orthopaedic Surgery Paediatric Orthopaedic section at Jinnah Postgraduate Medical Centre (JPMC) Karachi and Neurospinal Cancer Care Institute (NMI Hospital), Karachi Pakistan. The functional outcome was evaluated by Ferguson and Howarth rating system, McKay’s Criteria and Bhatti functional scoring system. The parameters compared were time consumed, patient’s compliance, difficulties incurred, functional limitations on clinical evaluation and its compatibility with the eastern lifestyle. Post stratification 2/2 table was used to calculate the Kappa statistics and accuracy.Results: The total number of patients in our study were 48. Male children were 9 (18.8%) and female 39 (88.3%). The mean age was 3 ± 1.45 years(range 2 to 7 years).Excellent outcome was noted in in 87.5%(n=42) patients and good in 6.2%(n=3) patients as per Ferguson Howarth and McKay’s criteria while 89.5%(n=43) patients had excellent outcome and 4.1%(n=2) good as per Bhatti scoring system. The compliance for Bhatti Scoring System was excellent to good in 48 (100%) patients and for Ferguson Howarth and McKay’s criteria 39 (81.25%) patients had excellent to good compliance. The mean time consumed for calculating the Ferguson and Howarth range of motion index was 6.31 ± 0.92 minutes while for of Bhatti scoring system it was 2.0 ± 0.26 minutes(P value